Adolescents who solely engage in online sexual experiences are at higher risk for compulsive sexual behavior. (July 2021) - Efrati, Yaniv; Amichai-Hamburger, Yair
Highlights: Adolescents who only engaged in online sexual activities had significantly higher percentage of CSB. Adolescents who engage in offline and online sexual activities had higher dominating and unsafe sexual action tendencies. Adolescents who engage in offline and online sexual activities report on lower attachment avoidance. Abstract: In addition to its expression offline, sexual behavior is frequently expressed online. Some adolescents solely engage in online sexual activities, whereas others in offline and online activities, or have no sexual experience at all. In the current research, we examined whether those who solely engage in online sexual activities are at greater risk for compulsive sexual behavior. In Study 1 ( n  = 164), we examined differences in compulsive sexual behavior (CSB) and risky sexual action tendencies between study groups. In Study 2 ( n  = 713), we statistically replicated the classification into different sexual behaviors and examined differences between the clusters in CSB, social tendencies and socio-demographic measures. Results indicated that adolescents who only engaged in online sexual activities had significantly higher percentage of clinical CSB, were less likely boys and more likely to be religious. There were not more prone to risky sexual behavior, however. The current research expands the knowledge about offline or online sexually related activities among adolescence.